NUEVO CINE ESPAÑOL: CINE, CINE, CINE, MÁS CINE, POR FAVOR* - Elena Medina de la Viña (Fonseca, Journal of Communication, 2023)
Change, new fiction, new methods of financing, low cost, are the usual cinema references when we talk about young and contemporary Spanish Cinema. Beside a time of increasing difficulty in financing films, we are experiencing a burst of creativity. We have also witnessed a technological change and a different public demand. Is it possible to find a model to enable sufficient economic return to continue enjoying movies?